Faculty development for teachers of family medicine in Europe: Reflections on 16 years' experience with the international Bled course - Bulc, Mateja (2009)
Background: Instruction in principles and methods of medical education is a core component of the training of medical teachers. Curricula for new medical teachers have developed across Europe, but few European courses have had the success of the EURACT Bled course for teachers of family medicine. The course focuses on practical issues in medicine and the professional development of physicians. This article describes 16 years' experience with the Bled course for teachers in general practice/family medicine (GP/FM). Course structure: The course is centred on the preparation of a teaching module, exploring a specific theme in family medicine. The main teaching methods used are: keynote lectures, small group sessions, field work and preparation of a teaching module by the participants. Outcomes: This course has attracted 555 participants from 20 countries since 1992. The course and its outputs have been applied in undergraduate and postgraduate teaching, and in continuous professional development (CPD) in several countries. It is a respected forum for faculty development. The experience of the Bled course suggests that academic medicine may be better able to fulfil its responsibilities by paying attention to relevant topics and using appropriate methods in undergraduate and postgraduate medical curricula.